Profiling Pre-Service Teachers’ Digital Literacy Levels: A Survey Research - Oni Setiawan Peranginangin; Rahma Dianti; Heru Setiawan (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2026)
The increasing use of digital technology in higher education has made digital literacy an essential skill, especially for students who are preparing to become teachers. This study aims to profile the level and the dimensions of digital literacy among pre-service teacher students of the Faculty of Teacher Training and Education at Tridinanti University. This research used a quantitative method with a cross-sectional survey design, involving 144 pre-service teacher students selected through total sampling. Data were collected using a Digital Literacy Scale (DLS), consisting of nine dimensions of digital literacy originally proposed by Chen (2015) and operationalized in the digital literacy scale developed by Amin et al. (2021). The obtained data were analyzed using mean score and percentage analysis. The results show that, in general, students already have a good level of digital literacy. The results of the percentage analysis showed that they tend to perform well in areas such as citizenship (ethical awareness), creativity, and collaboration in digital environments. However, some aspects, particularly those related to managing information and maintaining digital connections, are still not as strong. These findings indicate that although students are quite ready to participate in technology-based learning, there is still a need to improve their ability to critically evaluate and manage information. Overall, this study highlights the importance of strengthening digital literacy as part of teacher education programs.